2006
DOI: 10.1196/annals.1374.047
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rickettsia rickettsii and Rickettsia sp. in Blood Clots in 24 Patients from Different Municipalities of the State of São Paulo, Brazil

Abstract: The authors detected Rickettsia genus organisms using shell vial and polymerase chain reaction (PCR)/sequencing analysis in blood clots in patients suspected of having Brazilian spotted fever (BSF). DNA was detected using PCR with three sets of primers to access the gltA, ompA, and ompB genes. Sequence analysis was carried out using an automatic sequencer with Bioedit software. Seventy-five percent of the culture samples were positive and all samples amplified rickettsial gene fragments. To date, 46% of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The cases could be the consequence of better diagnostic tools, ecologic changes such as deforestation, human invasion into a wild environment, or suburbanization. 1,11 Alternatively, in the Yucatan Peninsula, the appearance and increase of human cases of RMSF could be caused by the introduction of domestic animals carrying ticks as a consequence of global trade from regions where infection with R. rickettsii occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The cases could be the consequence of better diagnostic tools, ecologic changes such as deforestation, human invasion into a wild environment, or suburbanization. 1,11 Alternatively, in the Yucatan Peninsula, the appearance and increase of human cases of RMSF could be caused by the introduction of domestic animals carrying ticks as a consequence of global trade from regions where infection with R. rickettsii occurs.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 20 years, a resurgence in identifi ed cases, accompanied by increasing interest in rickettsioses by Brazilian investigators and others, have intensifi ed the study of these diseases in this region [1,19,20]. Recently, Angerami et al [21] reported 23 patients with a confi rmed diagnosis of Brazilian spotted fever either by isolation of R. rickettsii from blood or skin (13 patients) or a fourfold rise in microimmunofl uorescence (MIF) titers (eight patients).…”
Section: Rickettsia Rickettsii Infection: New Aspects and Unanswered mentioning
confidence: 95%
“…Genomic DNA was extracted and polymerase chain reaction (PCR) was performed using primers to the rickettsial genes glt A (381pb) and omp A (532pb) [2].…”
Section: Methodsmentioning
confidence: 99%